AGAMA DAN POLITIK – HUBUNGAN YANG AMBIVALEN DIALOG VERSUS “BENTURAN PERADABAN”? - Mathias Daven (Ledalero Institute of Philosophy and Creative Technology (IFTK Ledalero), Indonesia, 2013)
At base, modern culture is a culture that evolves through the frame of managing non-violent normative conflict. With the acknowledgement of religious freedom as a basic human right, the state and religion have been distinguished institutionally: politics and the state no longer deal with truth, but rather with peace between people of different persuasions. In reality, the institutional distinction between religion and politics/the state has been translated into a variety of different political arrangements, including within the Muslim world; the relationship between politics and religion cannot return to a single (Western) model as the norm. Therefore an analysis of the correlation between religion and politics assumes an appropriate understanding about the relationship between religion and culture, for an analysis of the ties between religion and culture will more or less indicate the ambivalence of religion: on the one hand religions have the potential to critique culture; but on the other hand, religions play a very problematic role: they can take up a sacred form and tend to make absolute areas that are in fact relative, including politics. Religion refers to absolute truth and can be (mis)used in the interests of a religious political elite who collaborate with the political elite of the state which may be far from the key message of the religion in question. Nevertheless, an awareness of the ambivalence of religion and politics encourages us to collaborate between religions and cultures in order to lessen human suffering. Kata-kata Kunci: agama, politik, sekularisasi, modernisasi, ambivalensi, demokrasi, Sekularitas, hak asasi manusia, benturan peradaban, Fundamentalisme, dialog, etika derita.